2004
DOI: 10.1007/s11746-004-0926-3
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic epoxidation of methyl linoleate

Abstract: The epoxidation of methyl linoleate was examined using transition metal complexes as catalysts. With a catalytic amount of methyltrioxorhenium (4 mol%) and pyridine, methyl linoleate was completely epoxidized by aqueous H 2 O 2 within 4 h. Longer reaction times (6 h) were needed with 1 mol% catalyst loading. Manganese tetraphenylporphyrin chloride was found to catalyze the partial epoxidation of methyl linoleate. A monoepoxidized species was obtained as the major product (63%) after 20 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 18 publications
2
40
0
2
Order By: Relevance
“…Nevertheless, many heterogeneous catalysts and enzymes have been suggested and employed to augment the effects of organic acids and hydrogen peroxide to enhance the yield. It was also found that peroxy formic acid was more efficient than peroxy acetic acid (Du et al, 2004, Mungroo et al, 2008.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, many heterogeneous catalysts and enzymes have been suggested and employed to augment the effects of organic acids and hydrogen peroxide to enhance the yield. It was also found that peroxy formic acid was more efficient than peroxy acetic acid (Du et al, 2004, Mungroo et al, 2008.…”
Section: Introductionmentioning
confidence: 96%
“…Traditionally, an organic acid such as acetic or formic acid is used with hydrogen peroxide to generate per oxyacid as the oxygen carrier for the epoxidation of oils and fatty acid alkyl esters (Du et al, 2004). These per oxyacids can be employed as a separate reagent or can be synthesized insitu, but the most common method is the in-situ generation of peroxy acid.…”
Section: Introductionmentioning
confidence: 99%
“…The signal at 7.27 ppm referred to the solvent D 2 O for LA, MEOA and diepoxide LA [7]. Indeed, it appears that the signals were present in the MEOA, as four peaks of roughly equal intensity (132.89, 132.72, 130.15, and 124.02 ppm) were observed in the alkenic carbon region in the 13 C-NMR spectrum, [5], while they had disappeared in the di-epoxide LA.…”
Section: Ftir Analysis Of Meoamentioning
confidence: 96%
“…Increasing the temperature up to 60 °C also improved the rate of epoxide formation. The monoepoxidation of methyl linoleate was examined using transition metal complexes as catalysts [5]. With a catalytic amount of MTO (4 mol%) and pyridine, methyl linoleate was completely epoxidized by aqueous H 2 O 2 within 4 h. Longer reaction times (6 h) were needed with 1 mol% catalyst loading.…”
Section: Introductionmentioning
confidence: 99%
“…27 35 A presença de epóxidos cis ficou evidenciada pelo sinal dos hidrogênios oxirânicos observados em 2,9 ppm, sendo este característico de um autêntico grupo epóxido cis, pois os hidrogênios de um epóxido trans ressonariam em 2,63 ppm. 36 Isto indica que a configuração cis, presente na maioria dos ácidos graxos insaturados de matérias-primas renováveis, é mantida no correspondente epóxido. A reação 6 da Tabela 2 foi realizada com o catalisador no líquido iônico após ter sido utilizado na reação 5.…”
Section: Reação De Epoxidaçãounclassified